The Determined Criminal:From italian positivists criminologyto neuroscience - Medina Rico, Ricardo Hernán (2023)
This paper discusses the evolution of the study of criminology and the causes of delinquency ranging from the classic Italian positivists to the most relevant and current discussions that find their roots in neuroscience. The thesis proposed by the first determinists and the subsequent schools, whose theories were based on freedom and free choice, will be exposed from the historical recapitulation. Furthermore, this paper will address the American studies that base criminality on social, economic, and environmental aspects of the subject, always taking as starting point the human free will. Having considered surpassed the theories of Lombroso, Garófalo, and Ferri this paper will demonstrate, from natural sciences such as medicine and particularly neurology and forensic psychiatry, how the positivist principles could be relevant now and have an actual scientific basis. From the foregoing, this paper intends to give validity to the deterministic hypothesis that eliminate free will and consider that the offender does such conducts not because they chose to but because something bigger than them orders them to do so.